Memahami Pentingnya dan Menganalisis Penggunaan Biaya Berdasarkan Aktivitas serta Membedakannya Dengan Analisis Perhitungan Biaya Berdasarkan Tradisional atau Konvensional - Saudurma Silaban; Sherly Simanjuntak; Mey Reini; Pinta Siahaan; Hamonangan Siallagan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Cost is an important element in any organization, as it affects decisions and day-to-day operations. However, measuring and analyzing costs can be a challenging task, especially when costs are related to a specific activity or process. An activity-based costing approach is a way that can be used to address these challenges, by allowing management to better understand and control their costs more accurately and efficiently. By understanding cost-based activities, management can identify areas where they can reduce costs or improve efficiency, which can help organizations make better decisions about how to allocate their resources and improve their profitability. Activity-based cost calculation analysis involves measuring the costs associated with a particular activity and comparing them to traditional or conventional costs. This can help organizations understand the difference between activity costs and traditional costs, and identify areas where they can save costs or improve efficiency. Overall, the use of activity-based costs and the analysis of activity-based cost calculations can help organizations better understand and control their costs, make better decisions, and improve their profitability.